2020
DOI: 10.21203/rs.2.19917/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-Dimensional Morphological Analysis of the Femoral Neck Torsion Angle - An Anatomical Study.

Abstract: Background: The femoral neck torsion angle (FNTA) is a very important but often neglected parameter in assessments of the anatomical morphology of the femoral neck, and it is often confused with the femoral neck anteversion angle (FNAA) in the current literature. Currently, naked eye or two-dimensional literature (2D) visualization method was used in the literature that the measurement method reported, and the measurement parameters and details are not clearly defined. The objection of this research was to est… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The “inertia axis” method was used to determine the long and short axes of the FNI cross‐section 20–22 . Two perpendicular lines on the cross‐section of the FNI center on the inertial axes were defined as the long axes and short axes.…”
Section: Methodsmentioning
confidence: 99%
“…The “inertia axis” method was used to determine the long and short axes of the FNI cross‐section 20–22 . Two perpendicular lines on the cross‐section of the FNI center on the inertial axes were defined as the long axes and short axes.…”
Section: Methodsmentioning
confidence: 99%
“…In 1954, Billing [3]. clearly de ned FNA as the angle between the femoral neck axis and condylar plane (determined by the femoral shaft axis and the femoral condyle axis), which has been widely recognized [4]. With technology progresses, it is found that FNA is closely related to the hip stress and dysplasia, and is critical for the choice of surgical methods [5,6].…”
Section: Introductionmentioning
confidence: 99%